2018
DOI: 10.1016/j.arthro.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Lateral Acromioplasty Is Clinically Safe and Has the Potential to Reduce the Risk for Rotator Cuff Re-tears

Abstract: The critical shoulder angle and lateral acromioplasty are areas of controversy that are being studied in association with rotator cuff tears both as potential pathogenic variables and as surgically modifiable variables that could improve clinical outcomes. Current clinical evidence regarding the effectiveness and potential benefit of lateral acromioplasty support the hypothesis that modification of the bony anatomy may influence the integrity of the rotator cuff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“… 13 , 14 Thus, reduction of a large CSA to a “favorable” range of 30° to 34° may potentially prevent progression of rotator cuff tears or protect rotator cuff repair from re-tear. 15 Furthermore, subacromial spurs and sclerosis of the greater tuberosity are commonly encountered in shoulders with rotator cuff tears. 16 , 17 , 18 A subacromial osteophyte may enlarge the CSA and should therefore be included in measurement and therapy.…”
mentioning
confidence: 99%
“… 13 , 14 Thus, reduction of a large CSA to a “favorable” range of 30° to 34° may potentially prevent progression of rotator cuff tears or protect rotator cuff repair from re-tear. 15 Furthermore, subacromial spurs and sclerosis of the greater tuberosity are commonly encountered in shoulders with rotator cuff tears. 16 , 17 , 18 A subacromial osteophyte may enlarge the CSA and should therefore be included in measurement and therapy.…”
mentioning
confidence: 99%
“…3 Although the first results of changing the CSA have been published, we still do not know if changing the CSA is really beneficial in treating rotator cuff pain in the long term. 4,5 From recent placebo-controlled randomized trials and the BMJ Guideline, we can conclude that even sham surgery in patients with rotator cuff pain will lead to improvement in shoulder function. 6 Jones et al 7 recently concluded that high-quality randomized trials are needed before widespread adoption of promising operative procedures so as to avoid overtreatment and wasted resources.…”
mentioning
confidence: 99%
“…1 In their letter to the editor, van den Bekerom and Poolman 2 argue strongly against SAD and referenced several published trials in support. [3][4][5][6] We agree that there is no current and strong evidence to either support SAD or nonoperative treatment. In the introduction, we have clearly stated that credible, reliable, reproducible, and valid evidence is required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 27 , 50 Some authors suggested removing 5 or 10 mm of the lateral aspect of the acromion, solely in patients at high risk of retear (severe tendinopathy, thickness tear >50%) or those with large critical shoulder angles (ie, CSAs >35°). 28 , 35 Recent studies 20 , 33 criticized the use of such thresholds, arguing that small variations in patient position could significantly change the CSA on anteroposterior radiographs, and that in some cases acromioplasty may not decrease the CSA at all.…”
mentioning
confidence: 99%